2007
DOI: 10.1590/s1413-86702007000200021
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of newborn bacterial meningitis and sepsis during the pregnancy period for public health care system participants in Salvador, Bahia, Brazil

Abstract: Bacterial meningitis is still a major public health threat inside developing countries. In Brazil, the Department of Public Health estimates that the prevalence of bacterial meningitis is 22 cases per 100,000 persons. During the neonatal period, the bacterial meningitis develops special characteristics that can result in hearing problems and movement loss due to neurological and psychological damages. This study had the aim to analyze the prevalence of bacterial meningitis and sepsis in newborns during the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 23 publications
4
20
0
3
Order By: Relevance
“…In our study, 29 (52%) neonates with BM had late-onset infection, whereas Chang et al (2000) reported that from 85 patients, 51 (60%) were younger than 7 days old. Similarly, findings documented from Nigeria (Airede et al 2008), Australia (Francis and Gilbert 1992), Trinidad (Ali 1995), Brazil (Luzia et al 2007), Jordan (Daoud et al 1996) and Oxford (Hristeva et al 1993) indicated that low birth weight showed higher risk of neonatal bacterial meningitis and was significantly more likely in the preterm (p < 0.05). There is evidence to suggest that meningitis in preterm low birth weight and sickly babies is caused by organisms, usually from the maternal genital tracts (Delouvois 1994).…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…In our study, 29 (52%) neonates with BM had late-onset infection, whereas Chang et al (2000) reported that from 85 patients, 51 (60%) were younger than 7 days old. Similarly, findings documented from Nigeria (Airede et al 2008), Australia (Francis and Gilbert 1992), Trinidad (Ali 1995), Brazil (Luzia et al 2007), Jordan (Daoud et al 1996) and Oxford (Hristeva et al 1993) indicated that low birth weight showed higher risk of neonatal bacterial meningitis and was significantly more likely in the preterm (p < 0.05). There is evidence to suggest that meningitis in preterm low birth weight and sickly babies is caused by organisms, usually from the maternal genital tracts (Delouvois 1994).…”
Section: Discussionmentioning
confidence: 66%
“…Neonatal meningitis is an illness characterized as a result of infection of the meninges and it typically happens between birth and the first 28 days of life (Mohammad et al 2010; Luzia et al 2007; Delouvois et al 1991). Neonatal meningitis is an important cause of morbidity in sub-Saharan Africa and requires urgent empiric treatment with parenteral administered antibiotics (Olivia et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neonatal meningitis is the inflammation of the meninges typically occurring within the first 30 days of life [1]. It may be classified as early-onset (EOM) and late-onset meningitis (LOM) according to the time of diagnosis [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Krebs and Taricco studied 50 newborns with bacterial meningitis at the Children's Institute in São Paulo and showed that the medians for gestational age and weight at birth were 36 weeks and 2,577 g respectively, with a postnatal age of 13 days at the time of meningitis diagnosis 16 . At present, there is great concern about premature infants of gestational age greater than or equal to 34 weeks that show physiological and developmental immaturity and greater morbidity-mortality [17][18][19] . Studies on ontogeny and maturation sequence are being developed in an attempt to explain these patients' greater susceptibility to infection 20,21 .…”
Section: Discussionmentioning
confidence: 99%